Sosialisasi Kelas LIBUR (Kelas Ibu Balita Gibur) tentang Pemberian Makanan Tambahan pada Bayi Balita Gizi Buruk dan Kurang di Puskesmas Jenggot Kota Pekalongan - Pedvin Ratna Meikawati; Maslikhah Maslikhah (LPPM Akbid Harapan Ibu Pekalongan, 2020)
Toddler age (under five years) is an important period in the process of human growth and development, where in this period growth and development takes place very quickly. The process of growth and development of children that takes place quickly brings the consequences of increasing nutritional needs that are adequate. Poor nutrition is one of the factors that is significantly associated with an increased risk of acute respiratory infections, diarrhea, measles and several other infectious diseases. Such conditions will further worsen the nutritional status of children. If this continues, the risk of death in children will increase. Based on the Nutrition Program Report at the Pekalongan City Jenggot Health Center, in 2018 there were 13 infants with poor nutritional status 9 (BB / U) with 1 toddler with very thin nutritional status (BB / TB). This shows that there are still many children under five suffering from malnutrition (BB / U) and need special handling in overcoming this. This community service activity aims to increase the knowledge, attitudes and practices of toddlers about malnutrition and to compile healthy foods or snacks. Pretest and posttest were conducted to find out the knowledge of mothers who have babies and toddlers with poor and malnourished status. The results obtained are an increase in knowledge both mothers of children under five who after being given treatment, which was originally 33.3% to 60%. Routine Puskesmas to conduct classes for toddlers with varied in delivery, Academics or other related institutions, to always provide counseling for mothers of toddlers